República,guerra y represión : (Lucena 1931-1939) / Arcángel Bedmar González; prólogo de Francisco Moreno Gómez - Moreno Gómez, Francisco (1946-); Bedmar González, Arcángel
Bibliografía p. 205 -211Índices p. 215 - 232